2014
DOI: 10.1136/amiajnl-2013-002116
|View full text |Cite|
|
Sign up to set email alerts
|

ICD-10 codes used to identify adverse drug events in administrative data: a systematic review

Abstract: BackgroundAdverse drug events, the unintended and harmful effects of medications, are important outcome measures in health services research. Yet no universally accepted set of International Classification of Diseases (ICD) revision 10 codes or coding algorithms exists to ensure their consistent identification in administrative data. Our objective was to synthesize a comprehensive set of ICD-10 codes used to identify adverse drug events.MethodsWe developed a systematic search strategy and applied it to five el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(164 citation statements)
references
References 58 publications
1
138
0
19
Order By: Relevance
“…Hence, any estimated ADR incidence rates based on administrative data alone should be interpreted with caution. Nevertheless, we applied the most recent systematic review of ADR-related ICD-10 codes 18 , and limited our analysis to high-probability or very high-probability ADR diagnosis only. The study findings demonstrate a modest increase in hospitalised ADR incidence using relevant diagnosis codes in addition to external cause codes for identifying ADR-related hospitalisations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, any estimated ADR incidence rates based on administrative data alone should be interpreted with caution. Nevertheless, we applied the most recent systematic review of ADR-related ICD-10 codes 18 , and limited our analysis to high-probability or very high-probability ADR diagnosis only. The study findings demonstrate a modest increase in hospitalised ADR incidence using relevant diagnosis codes in addition to external cause codes for identifying ADR-related hospitalisations.…”
Section: Discussionmentioning
confidence: 99%
“…Results: Of 493 442 hospitalisations among 267 153 study participants during [2011][2012][2013]18.8% (n = 92 953) had hospital diagnosis codes that were potentially ADR related; 1.1% (n = 5305) had high/very highprobability ADR-related diagnosis codes (causality ratings: A1 and A2); and 2.0% (n = 10 039) had ADR-related external cause codes. Overall, 2.2% (n = 11 082) of cases were classified as including an ADR-based hospitalisation on either external cause codes or high/very high-probability ADR-related diagnosis codes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot rule out some degree of inaccuracy in reporting to the registers as physicians might misdiagnose ADE with unspecific clinical presentations, especially among older individuals [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these data sources and methods generate incomplete data that lack important clinical details [10,11]. For example, a validation study comparing trigger methods to prospectively collected ADE data found that only 2-15% of events were identifiable using trigger methods compared to prospective data collection [12][13][14].…”
Section: Introductionmentioning
confidence: 99%